Exploring the future for food security, agriculture and environments under climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Decision makers and researchers from Southeast Asia, one of CCAFS newest regions, met in Vietnam to debate how future climate, environmental, political and socio-economic factors could impact food security in the region. Read: https://ccafs.cgiar.org/blog/decision-makers-debate-climate-threats-southeast-asia From November 3 to 5 in Ha Long Bay,Vietnam organized by the FAO EPIC program, CCAFS, UNEP World Conservation Monitoring Centre, NOMAFSI and MARD, organised a workshop that brought regional stakeholders from development organizations, governments, private sector, civil society and academia together to outline scenarios on future socio-economic drivers of change for food security, environments and livelihoods in Southeast Asia to be considered together with future climate change. These scenarios can be used to help develop better policies and investments.